2019
DOI: 10.30651/st.v12i2.2802
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendekatan Higher Order Thinking Skill (HOTS) Terhadap Keterampilan Membaca Siswa Kelas X SMK Negeri 3 Kota Sukabumi

Abstract: Penelitian ini bertujuan untuk mengetahui bagaimana keterampilan membaca siswa setelah menggunakan pendekatan Higher Order Thinking Skill (HOTS). Jenis penelitian ini adalah kuantitatif dan desain penelitian yang digunakan pre experimental design dengan model  the one group pretest-posttest. Populasi penelitian kelas X SMK Negeri 3 Kota Sukabumi dengan sampel penelitian yang digunakan yaitu purposive sampling dan kelas yang dijadikan sampel penelitian yaitu X Jasa Boga I. Instrumen dalam penelitian ini menggun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Several previous studies support the findings of this study. The first study's results showed an influence of learning outcomes on students' thinking skills at the time of learning using the Higher Order Thinking Skill (HOTS) (Fazriani et al, 2019). Other research results showed that using HOTS-based students' worksheet books positively and significantly affects student learning motivation (Karsono, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies support the findings of this study. The first study's results showed an influence of learning outcomes on students' thinking skills at the time of learning using the Higher Order Thinking Skill (HOTS) (Fazriani et al, 2019). Other research results showed that using HOTS-based students' worksheet books positively and significantly affects student learning motivation (Karsono, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…In other words, students have the freedom to solve their problems using any media. Thus, students obtain their in-depth knowledge and understanding and independently learn (Fazriani et al, 2019;Ma'ruf et al, 2019).…”
Section: Blended Learning Of Stad and Jigsaw Towards Higher-order Thinking Skillsmentioning
confidence: 99%
“…According to the Teaching Knowledge Test Cambridge English, Higher-order Thinking Skills (HOTS) is the student's thinking ability consists of the ability to remember, restate, and refer without analyzing, examine information critically, creatively, be creative and be able to solve problems (Saliba et al, 2013). HOTS is the thinking skill that all vocational high school students in Indonesia must have (Fazriani et al, 2019). Vocational high school graduates must have the good soft skill and hard skill so that they could fully work after graduating (Fazriani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil analisis kemampuan berpikir kritis peserta didik diperoleh bahwa rata-rata kemampuan berpikir kritis peserta didik berada pada kategori sedang. Penelitian Fazriani et al,( 2019) menunjukkan Terdapat perbedaan yang signifikan terhadap hasil belajar siswa, dibuktikan dalam Uji-t diperoleh thitung > ttabel (13.69 > 2.042) dan uji Wilcoxon Sign rank yang menghasilkan nilai (asym.sig. (2-tailed)) adalah 0.000 < 0.05 maka hasil hipotesis H0 ditolak dan H1 diterima.…”
Section: Introductionunclassified